AVANCEMOS: Effects of school dropout in the Home of Beneficiaries - Muñoz-Alvarado, José Alfonso (2016)
The following paper shows the difference between the variables that explain school dropout in households in which at least one person is an AVANCEMOS beneficiary and in households where no member is. Furthermore, it seeks to demonstrate whether there is any effect on the program AVANCEMOS on siblings of a beneficiary in their decision to leave the educational system. Using The National Household Survey 2013 from INEC and through descriptive statistics and logistic models, we obtain results in which some variables that influence dropout such as area, quality of housing, basic services and gender have no influence in the same way households having AVANCEMOS or not. Meanwhile, age is always important for students when deciding to withdraw from the educational system regardless of the conditions of their home.  Moreover, being 18 years old is a critical age since it represents a breaking point in the decision of the student to continue studying or not.  If they come from an AVANCEMOS home, AVANCEMOS does not have any effect on siblings of beneficiaries of the program, but account to a higher proportion of students who leave school to go to work, 59.28%; against those who come from a home that does not participate in the program, which corresponds to a 48.35% of this population.